DEVELOPMENT OF ART AND CREATIVE ABILITIES OF PRESCHOOL CHILDREN THROUGH BOOKS - Nilufar Isroildjanovna Ismailova (Scholar Express Journal, 2022)
This article discusses the development of artistic and creative abilities of preschool children through books. Artistic activity is a free flight of imagination, imagination, intuition that can lead to inventions and discoveries. In the article, the author tried to prove that working with a book is the basis for the development of creative thinking
Keywords: Preschool Children; Work With Books; Artistic And Creative Abilities; Artistic Creation